THE SEARCH FOR MUSICAL IDENTITY IN POSTVOLVING MEXICO. FROM THE REGIONAL TO THE NATIONAL RHYTHMS - Cruz Carvajal, Cristina (2018)
This article deals with the period of the Post-revolutionary Mexico (1920-1940), where a situation of relative stability is experienced for the first time, causing that those in power sought, in coordination with the population of the nation, a musical style that identified Mexico in the international arena. Just as Spain is identified by flamenco, or Argentina by tango, Mexico is known by its mariachi music, or ranchera. Internally, this caused a dispute, since the country is very diverse, and several regional styles clash. For this reason, the emergence of nationalism is generated from the state, which motivated an internal characterization as well as a sense of identification towards what begins to mean Mexico. Thus, the present communication presents, from a historical perspective and through research of diverse sources, how the musical identity generated in Mexico still has repercussions today.